1998
DOI: 10.1152/jappl.1998.84.6.1882
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of contracting skeletal muscle after partial reduction of blood flow

Abstract: Hogan, Michael C., L. Bruce Gladden, Bruno Grassi, Creed M. Stary, and Michele Samaja. Bioenergetics of contracting skeletal muscle after partial reduction of blood flow. J. Appl. Physiol. 84(6): 1882-1888, 1998.-The purpose of this study was to examine the bioenergetics and regulation of O 2 uptake (V O 2 ) and force production in contracting muscle when blood flow was moderately reduced during a steadystate contractile period. Canine gastrocnemius muscle (n ϭ 5) was isolated, and 3-min stimulation periods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Thus, the Hb tot was always smaller in the leg up during the exercise, and the HbO 2 volume would also be smaller in leg up during the exercise. Hogan et al (1998) suggested that when stimulating the canine gastrocnemius muscle at a constant rate with a partial reduction of blood flow, the force generation would decrease according to the intracellular O 2 tension. Therefore, the steeper rise in iEMG, observed during FREE with the leg up, may be assumed to reflect the increased motor unit recruitment and/or discharge rate to counteract the decreased force generation capacity of the muscle caused by the reduction of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Hb tot was always smaller in the leg up during the exercise, and the HbO 2 volume would also be smaller in leg up during the exercise. Hogan et al (1998) suggested that when stimulating the canine gastrocnemius muscle at a constant rate with a partial reduction of blood flow, the force generation would decrease according to the intracellular O 2 tension. Therefore, the steeper rise in iEMG, observed during FREE with the leg up, may be assumed to reflect the increased motor unit recruitment and/or discharge rate to counteract the decreased force generation capacity of the muscle caused by the reduction of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle O 2 consumption of the diving emperor penguin is only approximately one-fifth that of canine gastrocnemius stimulated at 0.25Hz (Fig.9) (Hogan et al, 1998), less than onetenth the pectoralis-supracoracoideus muscle O 2 consumption calculated from emperor penguins swimming maximally in a flume (160ml O 2 kg -1 musclemin -1 ) (Kooyman and Ponganis, 1994;Ponganis et al, 1997a) and far less than maximal O 2 consumption of human quadriceps femoris muscle (520ml O 2 kg -1 musclemin -1 ) (Richardson et al, 1995b). Although muscle ischemia may contribute to decreased muscle O 2 consumption (see example in Fig.9) (Duran and Renkin, 1974;Hogan et al, 1998;, we hypothesize that biomechanical efficiency and hydrodynamics are primarily responsible for this low muscle O 2 consumption during diving of the emperor penguin.…”
Section: Muscle O 2 Consumption During Divesmentioning
confidence: 93%
“…Even in dives longer than the Weddell seal ADL, including a dive of 27min, Mb was typically still 40-60% saturated (Guyton et al, 1995). In contrast, saturation values in long type B dives often declined to below 10% (Fig.8) (Scholander et al, 1942) and canine gastrocnemius muscle stimulated at different rates (Hogan et al, 1998).…”
Section: Type B Mb Desaturation Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Impeding Vo 2 after the onset of exercise exaggerates the fall in muscle PCr and pH, increase in P i and loss of force production. [48][49][50][51] Therefore, it is likely that the slowing of the hyperaemic response (phase 2) contributes directly to the abnormal metabolic responses in contracting muscle and the loss of exercise tolerance in type 2 diabetes. 1-4, 6, 46 …”
Section: Relevance To Vo 2 and Exercise Tolerancementioning
confidence: 99%